Connecting knowledge and performance in public services : from knowing to doing - Walshe, Kieran; Harvey, Gill, RGN.; Jas, Pauline (Cambridge : Cambridge University Press, 2010)
'The performance of public services is now more closely scrutinised than ever before. Every teacher, doctor, social worker or probation officer knows that behind them stands a restless army of overseers, equipped with a panoply of league tables, star ratings, user opinion surveys, performance indicators and the like with which to judge them. This increased scrutiny and performance measurement has undoubtedly produced improved public services. Yet we still have a limited understanding about how this information can be best used to bring about improvements in performance. What goes on inside the'black box' of public organisations to move from information to action, or from'knowing' to'doing'? This book tackles this important question by reviewing a wide range of performance mechanisms. It explores how information about performance can be translated into improvements in services and, conversely, why this does not always happen in practice'--
Includes bibliographical references and index.
Keywords: Municipal services -- Management